Kinetic Spectrophotometric Determination of Ir(III) in Alkaline Medium - GOEL, ANJALI (Asian Journal of Chemistry, 2010)
A simple and sensitive spectrophotometric method has been developed for the determination of trace amount of Ir(III). The method is based on the Ir(III) catalyzed oxidation of glycine by hexacyanoferrate (III) in aqueous alkaline medium. Beer’s law is obeyed in the range of 1.99 to 39.98 μgcm-3 of Ir(III). The molar absorptivity and sandell’s sensitivity are found 0.50 × 103 to 1.1 × 103 L mol-1 cm-1 and 0.384 to 0.174 μg cm-2, correlation coefficient 0.9873 to 0.9968 and effect of few interfering ions have been worked out for developing the calibration curves in terms of absorbance or initial rates or pseudo first order rate constant vs. Ir(III) plot, λmax was 420 nm. The results show that the present method is more simple and sensitive than the reported methods and especially useful in absence of the expected interfering ions.